Multivitamin Use After Prostate Cancer Diagnosis Is Associated with Lower Risk of Recurrence: A Prospective Cohort Study from the Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) - Shee, Kevin; Cedars, Benjamin E.; Wang, Lufan; Kenfield, Stacey A.; Cowan, Janet E.; Tolstykh, Irina; Langlais, Crystal S.; Pace, William A.; Broering, Jeanette M.; Carroll, Peter R.; Chan, June M.; Van Blarigan, Erin L. (European urology oncology, 2025)
In a large multi-institutional cohort of 1396 men, postdiagnostic multivitamin use was strongly associated with lower risk of prostate cancer recurrence after surgery or radiation after adjustment for clinical factors. Multivitamin (MV) use is common among men with prostate cancer (PC). However, data on MV use in relation to the risk of PC recurrence are limited. We conducted a longitudinal observational cohort study in 1396 men with nonmetastatic PC who underwent radical prostatectomy (RP) or radiation therapy (RT) and enrolled in the Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) study between 1999 and 2018. The primary outcome was PC recurrence, defined as biochemical recurrence or initiation of secondary treatment. Postdiagnostic MV use was ascertained via a questionnaire after diagnosis and before any recurrence. Multivariable Cox proportional-hazards regression models controlled for sociodemographic factors, clinical factors, and health behaviors and were used to calculate adjusted hazards ratios (HRs) and 95% confidence intervals (CIs). In the study cohort there were 858 (62%) current MV users, 227 (16%) past MV users, and 311 (22%) never users. We observed 119 PC recurrence events over a median follow-up of 4.7 (interquartile range 1.9–9.2) yrs after survey completion. Current MV use was associated with lower risk of PC recurrence (basic model: HR 0.52, 95% CI 0.35–0.78; adjusted model: HR 0.51, 95% CI 0.33–0.78). In stratified analyses, the inverse association between current MV use and PC recurrence was stronger for men with grade group 2 (Gleason 3 + 4) or greater PC (n = 430; HR 0.27, 95% CI 0.13–0.55; p < 0.001) and was not statistically significant for men with grade group 1 (Gleason 3 + 3) PC (n = 966). MV use after PC diagnosis was associated with lower risk of PC recurrence, particularly in patients with higher-grade disease. This finding warrants validation and further investigation.